The Economic Value of Higher Education in Economic Growth against Labor Absorption and Human Development Index - Enny Diah Astuti; Ria Estiana; Sofia Maulida; Nika Sintesa (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Education is a key determinant of economic development and should be viewed as a long-term investment in improving the human development index. Weak support for the education sector can lead to issues such as unemployment, crime, drug abuse, and increased social dependency. This study examines the effect of completion levels in vocational, academic, and professional higher education on Indonesia’s economic growth, as well as its implications for labor absorption and human development index improvement. Using a quantitative approach, the study applies multiple linear regression and panel data analysis, with higher education completion rates as independent variables and economic growth as the dependent variable. The results show that completion levels in vocational, academic, and professional higher education have a significant effect on economic growth. In addition, economic growth has a positive and significant influence on labor absorption and human development index improvement. The findings confirm that increasing access to and the quality of higher education contribute substantially to national economic growth, which in turn plays a key role in reducing unemployment and enhancing the quality of life of the Indonesian population through improved human development index.